An Expert System to Mitigate Problems in University Using Chat Bot - Akhil, S; Sai Krishna, V; Kranthi, M; Nihar, A; S.Mastan Rao, T (International Journal of Engineering and Technology, 2018)
There has been a rapid increase in the data generated over the past few decades in all domains. As part of our research study we are considering domain of information provided by the university to the public i.e. the aspirants applying to the university as well as the students undergoing the curriculum. We are developing an advanced chat-bot which assists the students to gather information about the university. Since the information which can be provided from the official website is not up to the mark, there is a need for developing another medium for providing the necessary information. Whenever a student requires some assistance of any matter regarding university they can gather information from helpdesk, website or billboards. Sometimes the information may not be accurate and insufficient. So, in order to make the required information accessible to the students we are developing this software where students can interact with the software assistant through text and gain the information that is required by them. The software allows the student to interact with it in text basis and provides almost any information regarding University.Â Â